The Association between Addiction to Online Games and Students’ Academic Engagement: Determining the Mediating Role of Executive Function - Masoud Soltani Nazarlou; Mohammadagha Delavarpour; Seyed Musa Tabatabaee (International Journal of School Health)
Background: Online gaming addiction can negatively affect academic performance. Thus, it is important to understand the factors that influence it. This study aimed to investigate the correlation between online gaming addiction and academic engagement with the mediating role of executive functions among secondary school students.Methods: The present cross-sectional study included all secondary high school students in Tehran, Iran in the academic year of 2023-2024. A total number of 384 students were selected using the random cluster sampling method, and they were asked to fill out the Internet Gaming Disorder Test (IGD-20), Student Engagement Questionnaire, Adult Executive Functioning Inventory (ADEXI), and Nejati Cognitive Abilities Questionnaire. Data were analyzed using Pearson correlation analysis and structural equation modeling (SEM) with SPSS version 26 and AMOS version 24.Results: The results showed that online game addiction is negatively correlated with students’ academic engagement (r=-0.336) as well as all dimensions of executive function, including planning (r=-0.425), cognitive flexibility (r=-0.455), working memory (r=-0.420), and inhibition (r=-0.350). Furthermore, path analysis revealed that online game addiction does not directly predict academic engagement (β=-0.12, P=0.37). However, it can indirectly predict academic engagement through the mediation of working memory (β=-0.013, P=0.025) and inhibition functions (β=-0.013, P=0.016). Overall, addiction to online games and the dimensions of executive function collectively account for nearly 44% of students’ academic engagement.Conclusions: These results suggested that excessive online gaming is destructive to cognitive abilities and motivation toward learning and schooling among adolescent students. Consequently, parents, teachers, and school psychologists should develop suitable educational, training, and therapeutic strategies to mitigate these harmful effects.